Peronospora hyoscyami f. sp. tabacina. Variabilidad morfologica en esporangios de aislados - Muiño Garcia, B.L.=700 1 Gonzalez Guardiola, Y.
(Es, En)
Ilus., 7 ref.
Keywords: NICOTIANA TABACUM; PERONOSPORA TABACINA; ESPORANGIOS; CUBA; PERONOSPORA HYOSCYAMI; VARIACION MORFOLOGICA